2014
DOI: 10.1016/j.gie.2014.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of response to endoscopic therapy of Barrett’s dysplasia by using genetic biomarkers

Abstract: Background Endoscopic therapy for the treatment of high-grade dysplasia (HGD) and intramucosal cancer (IMC) in Barrett’s esophagus (BE) may not always result in complete remission of dysplasia (CRD). Objective To determine if genetic alterations in the Barrett’s mucosa can predict response to endoscopic therapy. Design Retrospective cohort study. Setting Tertiary-care institution. Patients Selected patients who underwent endoscopic therapy for BE containing HGD/IMC between 2003 and 2010. Intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 32 publications
1
24
0
Order By: Relevance
“…There were 130 patients (72 %) who responded to endoscopic eradication therapy and achieved complete remission of dysplasia. Multiple gains detected by FISH was found to be a significant negative for achieving this endpoint (hazard ratio 0.57; 95 % CI 0.4 -0.82) [58]. While the results of this study are not conclusive, it paves the path for future studies to evaluate predictive biomarker panels for endoscopic eradication therapy patient selection and surveillance post endoscopic eradication therapy.…”
Section: Fluorescence In Situ Hybridization (Fish)-based Biomarkersmentioning
confidence: 68%
“…There were 130 patients (72 %) who responded to endoscopic eradication therapy and achieved complete remission of dysplasia. Multiple gains detected by FISH was found to be a significant negative for achieving this endpoint (hazard ratio 0.57; 95 % CI 0.4 -0.82) [58]. While the results of this study are not conclusive, it paves the path for future studies to evaluate predictive biomarker panels for endoscopic eradication therapy patient selection and surveillance post endoscopic eradication therapy.…”
Section: Fluorescence In Situ Hybridization (Fish)-based Biomarkersmentioning
confidence: 68%
“…In a cohort of 181 patients undergoing radiofrequency ablation, the same FISH panel found that the presence of multiple gains at baseline predicted failure of complete remission of dysplasia (hazard ratio [HR] 0.57, 95% CI 0.40-0.82). 103 As pointed out earlier, if these changes are irreversible, use of these markers may spuriously underestimate the chemopreventive potential of an agent. Contrary to this, epigenetic effects, such as global hypomethylation and promoterspecific hypermethylation that are more dynamic in nature, or microRNA will likely be better markers to assess the efficacy of a chemopreventive agent.…”
Section: Surrogate Endpoint Biomarkersmentioning
confidence: 97%
“…[66][67][68] A recent retrospective study showed that the presence of multiple gains detected by brush cytology specimens and FISH was a negative predictor to response rate for endoscopic therapy. 69 Concomitant treatment of acid reflux with PPIs and continuous surveillance are essential for better success outcomes and maintaining the stability of the neosquamous epithelium. However, prior fundoplication did not improve safety and efficacy outcomes for patients undergoing RFA.…”
Section: Current Controversies/future Considerationsmentioning
confidence: 99%